2009
DOI: 10.1097/tp.0b013e318192df6b
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Warm Ischemic Rat Liver Grafts by Normothermic Extracorporeal Perfusion

Abstract: Background Liver transplantation is currently the only established treatment for end-stage liver disease, but it is limited by a severe shortage of viable donor livers. Donors after cardiac death (DCD) are an untapped source that could significantly increase the pool of available livers. Preservation of these DCD livers by conventional static cold storage (SCS) is associated with an unacceptable risk of primary non-function and delayed graft failure. Normothermic extracorporeal liver perfusion (NELP) has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 41 publications
6
70
1
1
Order By: Relevance
“…These findings are important for several reasons. First, NMP is rapidly becoming the subject of preclinical and clinical research (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Second, different research groups have used various perfusion protocols but none have compared their efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are important for several reasons. First, NMP is rapidly becoming the subject of preclinical and clinical research (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Second, different research groups have used various perfusion protocols but none have compared their efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen consumption (VO 2 ) was calculated using partial pressure of oxygen , hemoglobin saturation and blood flow, as specified by the formula described by Tolboom et al (15). The volume of bile production was recorded.…”
Section: Outcome Measures: Preservation Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Поскольку пере садка печени является «хирургией одного шанса», то повышаются требования к методам верификации качества трансплантата перед операцией. Мини мизация нежелательных изменений в донорском органе могла бы быть достигнута за счет создания перфузионных устройств, с помощью которых воз можно проведение искусственного кровообраще ния для селекции, «лечения» и поддержания жиз неспособности in situ и ex vivo [4,6,7,10,12,13].…”
Section: Introductionunclassified
“…Gong et al 13 reported that pig livers undergoing normothermic machine perfusion were significantly more viable than those stored in cold histidine-tryptophan-ketoglutarate solution. In a rat model, Tolboom et al 14 found that normothermic liver perfusion optimized the preservation of DCD livers.…”
Section: Commentsmentioning
confidence: 99%